2015
DOI: 10.1371/journal.pone.0135220
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Imaging of Orthotopic Mouse Model of Endometrial Carcinoma

Abstract: BackgroundOrthotopic endometrial cancer models provide a unique tool for studies of tumour growth and metastatic spread. Novel preclinical imaging methods also have the potential to quantify functional tumour characteristics in vivo, with potential relevance for monitoring response to therapy.MethodsAfter orthotopic injection with luc-expressing endometrial cancer cells, eleven mice developed disease detected by weekly bioluminescence imaging (BLI). In parallel the same mice underwent positron emission tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 27 publications
(35 reference statements)
1
52
0
Order By: Relevance
“…Interestingly, PDX4 developed a uterine tumor that was clearly depicted on EpCAM-AF680 NIRF images ( Figure 5D), despite the primary tumor sample for that PDX exhibiting low expression of EpCAM on IHC (SI: 4). PDX mice had suspected uterine tumors based on visual inspection of reconstructed 18 F-FDG PET/CT images ( Figure 5A-D, Figure S2). However, in several of the scans from PDX1-3, suspected lesions had standardized uptake values (SUV) below 2.5, which was the threshold used to define tumors in PET images ( Figure 5A-C, Figure S2).…”
Section: In Vivo Epcam-af680 Nirf Imaging Detects Uterine Tumors In Pmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, PDX4 developed a uterine tumor that was clearly depicted on EpCAM-AF680 NIRF images ( Figure 5D), despite the primary tumor sample for that PDX exhibiting low expression of EpCAM on IHC (SI: 4). PDX mice had suspected uterine tumors based on visual inspection of reconstructed 18 F-FDG PET/CT images ( Figure 5A-D, Figure S2). However, in several of the scans from PDX1-3, suspected lesions had standardized uptake values (SUV) below 2.5, which was the threshold used to define tumors in PET images ( Figure 5A-C, Figure S2).…”
Section: In Vivo Epcam-af680 Nirf Imaging Detects Uterine Tumors In Pmentioning
confidence: 99%
“…Thus, PDX models are not only anticipated to capture both the intra-and inter-tumor heterogeneity of endometrial carcinoma, as has been previously demonstrated for breast, lung and pancreatic cancer, but also to faithfully reproduce clinical responses to chemotherapy [16,17]. Critically, orthotopic PDX models, i.e., where primary biopsies are implanted into the organ/microenvironment of origin, are proposed as a superior paradigm of clinical disease compared with subcutaneous PDX [18][19][20]. However, a major caveat of the orthotopic approach, particularly with patient-derived material, is longitudinal and spatio-temporal monitoring of not only disease development and characterization but also for further intervention studies.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…It is a form of quantitative whole-body imaging used for the in vivo monitoring of biological processes, such as enzymatic reactions, cellular metabolism, and cell proliferation and migration [41], which makes it an ideal tool for the imaging of cancer [32,42]. …”
Section: Endometrial Cancer Pdx Modelsmentioning
confidence: 99%